1981
DOI: 10.1128/iai.34.1.120-125.1981
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Neisseria meningitidis infection in mice by addition of iron bound to transferrin

Abstract: Small quantities of iron bound specifically to human transferrin were found to stimulate infection with Neisseria meningitidis strain M1011 in mice. An intraperitoneal injection of 17.5 mg of transferrin carrying 22.7 ytg of Fe resulted in 100% mortality from infection, as compared with no mortality for the controls which had received saline. Five milligrams of ferri-transferrin (FeTf), carrying 6.5 yg of Fe, stimulated and prolonged bacteremia in the mice. Thus, FeTf maintained infection, whereas infection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 18 publications
4
48
0
1
Order By: Relevance
“…The receptor for transferrin is iron regulated, and seems to be highly specific for human transferrin [1471. Furthermore, it has been described that injection of human transferrin has a very important impact in the development of experimental infections by meningococci in mice [141]. These data may explain the host specificity of this pathogen as Neisseria meningitidis is normally apathogenie for mice.…”
Section: Iron Acquisition From the Iron-binding Proteins Of The Hostmentioning
confidence: 90%
See 1 more Smart Citation
“…The receptor for transferrin is iron regulated, and seems to be highly specific for human transferrin [1471. Furthermore, it has been described that injection of human transferrin has a very important impact in the development of experimental infections by meningococci in mice [141]. These data may explain the host specificity of this pathogen as Neisseria meningitidis is normally apathogenie for mice.…”
Section: Iron Acquisition From the Iron-binding Proteins Of The Hostmentioning
confidence: 90%
“…it has been shown that the availability of iron influences the virulent properties of Neisseria meningitidis [139][140][141]. Although Neisseria seems not to produce siderophores |142-144], Neisseria meningttidJs might acquire iron from transferrin [143][144][145] and iactofcrrin [146] through specific membrane receptors [147,148].…”
Section: Iron Acquisition From the Iron-binding Proteins Of The Hostmentioning
confidence: 99%
“…Human apotransferrin was purchased from Sigma Chemical Co. Human diferric transferrin (Fe-Tf) was prepared essentially as described by Holbein [21]. Briefly, 0.025/xmol of FeC13 complexed with 0.25/~mol of sodium citrate and 1 mg of Tf were diluted in 40 mM Tris (hydroxymethylaminomethane)-chloride buffer (Tris.…”
Section: Preparation Of Diferric Tf For Affinity Chromatographymentioning
confidence: 99%
“…These pathogens can directly bind the host's ironbinding proteins such as lactoferrin, transferrin, and haem-containing compounds, and use them as sole sources of iron, Neisseriae meningitidis is one of the leading causes of bacterial meningitis in children and heaithy adults in the worid. The severity of the disease is epitomised by the ability of meningococci to cause the death of previously healthy individuals in less than 24 h. The importance of iron in the virulence of N. meningitidis was dsmonstrated by in vivo studies using mice as the animal model system (Oalver etat., 1976;Holbein, 1981). Specific ironregulated outer membrane receptors have been shown to be involved in the binding and the utilization of lactoferrin-and transferrin-lron in neisseriae (Schtyvers and Morris, 1988a.b;Legrain el al., 1993;Pettersson et at., 1993;.…”
Section: Introductionmentioning
confidence: 99%